2000
DOI: 10.1580/1080-6032(2000)011[0012:mwpwtu]2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological water purification without the use of chemical disinfection

Abstract: These units comply with the criteria guidelines for microbial removal under the United States Environmental Protection Agency's "Guide Standard and Protocol for Testing Microbiological Water Purifiers."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In this study, only the poliovirus type 1 was used to reduce the cost of the testing and was based on our 30 years of experience with the USEPA protocol testing both rotavirus SA-11 and poliovirus type 1. Our previous studies have shown that if poliovirus type 1 is removed by 4 logs, so is the rotavirus SA-11 (Abbaszadegan et al 1997;Gerba et al 1997;Naranjo et al 1997;Gerba and Naranjo 2000;Abd-Elmaksoud et al 2013). This of course does not mean that there may be systems that would be less effective against poliovirus type 1 than rotavirus SA-11.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only the poliovirus type 1 was used to reduce the cost of the testing and was based on our 30 years of experience with the USEPA protocol testing both rotavirus SA-11 and poliovirus type 1. Our previous studies have shown that if poliovirus type 1 is removed by 4 logs, so is the rotavirus SA-11 (Abbaszadegan et al 1997;Gerba et al 1997;Naranjo et al 1997;Gerba and Naranjo 2000;Abd-Elmaksoud et al 2013). This of course does not mean that there may be systems that would be less effective against poliovirus type 1 than rotavirus SA-11.…”
Section: Discussionmentioning
confidence: 99%
“…The worst case water matrix with defined total dissolved solids (TDS = 1500 mg L −1 ), total organic carbon (TOC = 10 mg L −1 ), and turbidity (30 NTU) was prepared from sea salts, humic acid, and fine test dust, respectively, according to the standardized guide protocol (USEPA, 1987; Gerba and Naranjo, 2000). Sea salts (S9883; Sigma, St. Louis, MO) were prepared in distilled water, to which humic acid (H16752; Sigma‐Aldrich, St. Louis, MO) and fine test dust (ISO 12103‐1; Powder Technology Inc., Burnsville, MN) were added to standard TDS, TOC, and turbidity levels, as listed above.…”
Section: Methodsmentioning
confidence: 99%
“…The model used EPA worst case water, a defined medium originally developed and approved for testing point‐of‐use microbiological water purifiers (USEPA, 1987). Like effluent, the worst case water contained high levels of dissolved salts, organic carbon, and turbidity (Gerba and Naranjo, 2000). Control of Salmonella by phages was demonstrated in the worst case water model system and is believed to be a new application of worst case water tests.…”
mentioning
confidence: 99%
“…From this, it is apparent that no single combination of adsorbent/adsorption conditions exists to give optimum reduction of all viruses for all water qualities (reference 12). Increasing electrostatic and or hydrophobic interactions by the addition of chemicals such as magnesium sulfate (reference 13) or by specially treating the filter to promote a positive charge at natural water pH will increase virus retention (references [14][15][16][17]. One study investigating coliphage reduction by a 0.2 µm microporous filter, showed reduction based on adsorption as well as size exclusion (reference 9).…”
Section: Role Of Pathogen In Filtration Separation Mechanismsmentioning
confidence: 99%